2012
DOI: 10.5194/acp-12-7285-2012
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei activity of fresh primary and aged biomass burning aerosol

Abstract: Abstract. We quantify the hygroscopic properties of particles freshly emitted from biomass burning and after several hours of photochemical aging in a smog chamber. Values of the hygroscopicity parameter, κ, were calculated from cloud condensation nuclei (CCN) measurements of emissions from combustion of 12 biomass fuels commonly burned in North American wildfires. Prior to photochemical aging, the κ of the fresh primary aerosol varied widely, between 0.06 (weakly hygroscopic) and 0.6 (highly hygroscopic). The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
136
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 36 publications
16
136
3
Order By: Relevance
“…Results for D 0 = 110 nm are similar, except for a vanishing contribution of the more-hygroscopic background mode and a broader and slightly more hygroscopic fresh emissions mode (peaking between GF ≈ 1.15-1.3). These observations are consistent with variable, but moderate hygroscopicity of fresh biomass burning emissions from different sources (e.g., Petters et al, 2009;Engelhart et al, 2012;Martin et al, 2013). Condensation of secondary organic and inorganic matter on the primary particles in the concentrated biomass burning plume may also contribute to slightly larger GFs at smaller dry sizes.…”
Section: Aerosol Hygroscopicitysupporting
confidence: 75%
“…Results for D 0 = 110 nm are similar, except for a vanishing contribution of the more-hygroscopic background mode and a broader and slightly more hygroscopic fresh emissions mode (peaking between GF ≈ 1.15-1.3). These observations are consistent with variable, but moderate hygroscopicity of fresh biomass burning emissions from different sources (e.g., Petters et al, 2009;Engelhart et al, 2012;Martin et al, 2013). Condensation of secondary organic and inorganic matter on the primary particles in the concentrated biomass burning plume may also contribute to slightly larger GFs at smaller dry sizes.…”
Section: Aerosol Hygroscopicitysupporting
confidence: 75%
“…Accumulation type aerosol was connected to long-range transport from the Sahara and Sahel region, where either mineral dust from the desert and/or biomass-burning particles from the Sahel were involved in raising the particle number concentrations in the accumulation mode. Although particles from both biomass burning and mineral dust are sometimes assumed to be of rather insoluble nature, they have been shown to contribute to CCN (Engelhart et al, 2012;Twohy et al, 2009;Karydis et al, 2011), and an increase in N CCN due to their presence was also observed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding the indirect effect, particles that are larger in diameter and more hygroscopic are more likely to act as CCN (Petters and Kreidenweis, 2007). Typically, particles larger than 30-100 nm act as CCN depending on conditions and hygroscopicity (Petters and Kreidenweis, 2007;Petters et al, 2009), though this range may be slightly larger or smaller for fresh biomassburning particles due to these particles being initially more hydrophobic/hydrophilic (depending on fuel type) than typical ambient aerosol Engelhart et al, 2012;Petters and Kreidenweis, 2007). Furthermore, for constant emissions mass, a factor-of-2 change in diameter leads to a factor-of-8 change in number emissions, which may contribute to significant changes in CCN concentrations (Pierce et al, 2007;Spracklen et al, 2011).…”
Section: Biomass-burning Particlesmentioning
confidence: 99%